A Combination of Back Massage Frirage and Acupressure on Accelerating the Time of Breastmilk Production and Adequate Breastmilk for Babies - Triana Septianti Purwanto; Feby Angzila Fatmayati (Alliance oh Health Activists (AloHA), 2024)
Failure to produce breastmilk in the first days can interfere with early breastfeeding. In 2017, 44% of infants get prenatal meals 3 days after birth. The study was using a complementary technique of combination back massage frirage and acupressure to speed up the breastmilk production and increase the breastmilk supply to the baby so that we can prevent stunting in the baby. Researchers had done a quasi-experimental with a post-test design only with a control group design. The size sample of 60 mothers after giving birth and their babies with sample size of each group was 30 respondents, selected using systematic random sampling. Data collection was using an interview checklist for breastmilk extraction times and sufficient breastmilk for the baby. The researcher conducted an analysis of data using Mann Whitney U and independent samples t-tests. In the results of this study, there was an effective combination of back massage frirage and acupressure techniques on accelerate breastmilk production and increase breastmilk requirements for babies (p-value